Cancer Karyotypes: Survival of the Fittest - Nicholson, Joshua M.; Cimini, Daniela (Frontiers in Oncology, 2013)
Cancer cells are typically characterized by complex karyotypes including both structural and numerical changes, with aneuploidy being a ubiquitous feature. It is becoming increasingly evident that aneuploidy per se can cause chromosome mis-segregation, which explains the higher rates of chromosome gain/loss observed in aneuploid cancer cells compared to normal diploid cells, a phenotype termed chromosomal instability (CIN). CIN can be caused by various mechanisms and results in extensive karyotypic heterogeneity within a cancer cell population. However, despite such karyotypic heterogeneity, cancer cells also display predominant karyotypic patterns. In this review we discuss the mechanisms of CIN, with particular emphasis on the role of aneuploidy on CIN. Further, we discuss the potential functional role of karyotypic patterns in cancer.